Molecular diagnosis of high-risk Human Papilloma Virus infection in a South African patient cohort - Earle, Hendrik (My University, 2018)
Molecular pathology laboratories use DNA and mRNA PCR assays to detect hrHPV infections that are associated with carcinomas. The objective of this study was to determine the prevalence of HPV sub-types in HPV E6/E7 mRNA positive samples from the study cohort. HPV DNA genotyping was used to determine HPV prevalence. Epidemiological studies are important for public health, because they focus on the patterns of disease occurrence and the factors that influence these patterns. A total of 160 LBC samples, sent for routine screening of HPV E6/E7 mRNA were used for this observational descriptive study. Demographic information indicated that the samples had been collected from Gauteng and Limpopo provinces. The ages of the patients varied from 18 years to 73 years and patients’ ethnicities were seldom listed. HPV DNA genotyping results indicated that HPV 16 with a result of 18.83% was the most common HPV sub-type detected and this prevalence of HPV 16 was consistent with findings reported in the literature. HPV 59 was the second-most commonly HPV sub-type detected with a result of 13.64%. HPV 18 had a relatively lower prevalence result of 6.49%, together with HPV 51 and was ranked as the ninth commonest HPV sub-type. The 10 most prevalent HPV sub-types detected in this study were all from group 1A carcinogens, except for one, HPV 35, that was detected as 6 most commonest HPV sub-type with a percentage of 9.09 %. The results indicate that the new 9vHPV vaccine would be beneficial for South Africa because it vaccinate against 4 of the 5 most prevalent HPV sub-types detected in this study.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirements for the degree of Masters of Science in medicine. Johannesburg, 2018